PENGARUH RASIO PROFITABILITAS, UKURAN PERUSAHAAN DAN LEVERAGE TERHADAP PERINGKAT OBLIGASI (StudiEmpirisPada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Periode 2010 â 2014) - Feni Patria Nida, 12.05.51. 0148; Parmono Hadi, Teguh (Students Journal of Economic and Management, 2016)
This research aims to investigate the influence of the ratio profitability, company size (firmsize), and leverage to bond rating. The financial performance consisted of profitability (return on equity), firm size (total assets), and leverage (DER) . The sampels in this research were obtained by using purposive sampling method that consists of bonds issued by companies listed on the Stock Exchange the period 2010- 2014 and rated by PT Pefindo. This reserach uses a model of logistic regression analysis.Results of this test proves the profitability ratios significant positive effect on bond ratings, while the size of the company and leverage is a variable that does not affect the bond ratings. Keywords: bond ratings, profitability, firm size, leverage